Pengelolaan Sampah Dari Rumah Sebagai Upaya Pelestarian Lingkungan di Desa Belumbang Tabanan Bali - Luh Gede Putri Kusuma Pekerti; Ni Luh Putu Sri Widhiastuty; I Putu Yogi Anto Wijaya (Prosiding Seminar Nasional Riset dan Pengabdian pada Masyarakat, 2024)
Waste management is a major concern in many areas. The residents of Belumbang Village have limited knowledge regarding waste and its management. Insufficient supporting facilities exacerbate this issue, resulting in a significant annual budget for waste collection. Therefore, it is crucial to foster awareness among residents to avoid indiscriminate waste disposal and educate them on waste segregation. Stemming from these challenges, this KKNT activity aims to provide solutions by educating the community on the importance of maintaining cleanliness, segregating organic and inorganic waste, and utilizing waste to create economic value. The outputs of this activity include awareness-raising signboards and the provision of segregated trash bins. The method used is qualitative, with activities involving observation and interviews with the village head regarding the waste issues in Belumbang. The results of this KKNT activity indicate increased community awareness of cleanliness, enhanced understanding of independent waste segregation, and knowledge of its benefits.